Remarkable sexual dimorphism found in Nosophora insignis (Butler) (Lepidoptera, Crambidae, Spilomelinae) - Matsui, Yuki; Kohama, Sari; Naka, Hideshi (Zootaxa, 2024)
An unidentified spilomeline moth, “Nosophora sp.” was first illustrated by Inoue (1982) from Japan. Since little is known about the immature stage of “Nosophora sp.”, we attempted to rear this species from eggs. As a result, we found that “Nosophora sp.” can be successfully reared on Quercus serrata Murray and Q. glauca Thunb. Surprisingly, of the adults that emerged, all females showed the “Nosophora sp.” phenotypes, while all males showed the N. insignis (Butler, 1881) phenotypes. We also found that the mitochondrial COI sequences of “Nosophora sp.” and N. insignis are completely identical. Based on these results, we concluded that “Nosophora sp.” and N. insignis represent the sexual dimorphisms of the same species, and redescribed N. insignis.